POLISH TEACHERS ON EXTRACURRICULAR EDUCATION (ITS GOALS, FUNCTIONS, CONTENT, FUNDAMENTALS, METHODS, FORMS) - Savchenko Н.С. (Pedagogy of Higher and Secondary Education, 2022)
The article acguuints vith essence. functions. bases and organizational forms of extracurricular and out-of-school employments, thai is one of substantial elemenis of structure of pedagogical knowledges of the Polish teachers.